2014
DOI: 10.1063/1.4868221
|View full text |Cite
|
Sign up to set email alerts
|

A violet emission in ZnS:Mn,Eu: Luminescence and applications for radiation detection

Abstract: Articles you may be interested inTunable emission in surface passivated Mn-ZnS nanophosphors and its application for Glucose sensing AIP Advances 2, 012183 (2012); 10.1063/1.3698310Temperature and pressure behavior of the emission bands from Mn-, Cu-, and Eu-doped ZnS nanocrystalsWe prepared manganese and europium co-doped zinc sulfide (ZnS:Mn,Eu) phosphors and used them for radiation detection. In addition to the red fluorescence at 583 nm due to the d-d transition of Mn ions, an intense violet emission at 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
12
1
Order By: Relevance
“…1A ,B). They are cost-effective, easy to synthesize, and readily embedded or coated onto glasses 7 8 9 . When illuminated by a UV light source, they convert UV light to narrow-band green or red light, or wide-spectrum white light ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A ,B). They are cost-effective, easy to synthesize, and readily embedded or coated onto glasses 7 8 9 . When illuminated by a UV light source, they convert UV light to narrow-band green or red light, or wide-spectrum white light ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ZnS is an excellent luminescence host material and, frequently, transition and rare‐earth (RE) metal impurities are doped in the ZnS host to obtain impure luminescence. In recent years, however, it has been reported that doping of transition and RE metal impurities can greatly enhance the luminescence intensity of ZnS materials . For example, Yang et al reported that emission intensities increased by about five to six times in ZnS nanocrystallites after doping with Ce, Y, Nd, Er and Tb metal ions .…”
Section: Introductionmentioning
confidence: 99%
“…Sridevi et al reported that the fluorescence intensities of ZnS nanoparticles, doped with La, Mn, Co. and Ni metal ions, were five to six times that of pure ZnS . Importantly, it has been reported more recently that doping of Eu 2 + can increase the luminescence of ZnS materials . Ashwini et al reported that the luminescence intensity in ZnS:Eu 2 + nanoparticles was enhanced with increasing doping concentrations of Eu 2 + .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intense emission from ZnS layer not only is used for solid state lighting but also offers a very sensitive method for radiation detection [8]. Hence, the importance of excitation enhancement in PL layers is highlighted.…”
Section: Introductionmentioning
confidence: 99%